2016
DOI: 10.1039/c6py00164e
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of morphology transition of di-block copolymer nano-objects via RAFT dispersion copolymerization

Abstract: Promotion of morphology transition of di-block copolymer nano-objects was achieved via RAFT dispersion copolymerization because of the enhancement of the mobility of the solvophobic block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 49 publications
1
42
0
4
Order By: Relevance
“…Besides, the high T g value of PPyMA limits its mobility in the dispersion mixture, which consequently restricts the morphology transition to obtain higher order morphologies, such as vesicles. This is in good agreement with previously reported RAFT dispersion polymerization of polystyrene with high T g values …”
Section: Methodssupporting
confidence: 93%
“…Besides, the high T g value of PPyMA limits its mobility in the dispersion mixture, which consequently restricts the morphology transition to obtain higher order morphologies, such as vesicles. This is in good agreement with previously reported RAFT dispersion polymerization of polystyrene with high T g values …”
Section: Methodssupporting
confidence: 93%
“…Factors that may facilitate the exchange of polymer chains between nano‐aggregates include: i) a relatively low (ideally sub‐ambient) bulk glass transition temperature (T g ) of the core block; and ii) the relevant degree of solvation of the polymer core. It has been reported that core‐forming blocks with sub‐ambient T g 's may lead to increased polymer chain flexibility which can allow for facile rearrangement . Additionally, solvent or/and monomer can be also used to swell the polymer core as a direct result of a surface plasticizing effect (see section ) of the core‐forming block and in turn change the packing parameter.…”
Section: General Considerationsmentioning
confidence: 99%
“…). The reaction mixture was transparent at the beginning, but became milky white as the reaction proceeds, indicating a step‐wise change in nano‐particle morphology with increasing DP n of the PBzMA block . An aliquot from the reaction vial was periodically taken out using a N 2 purged syringe at different time interval and monomer conversions were determined from 1 H NMR spectroscopy by comparing the integration ratio of poly(benzyl methacrylate) (PBzMA) C H 2  peak at δ = 4.9 ppm to BzMA vinyl (C H 2 CH) peak at δ = 6.12 and 5.72 ppm.…”
Section: Resultsmentioning
confidence: 99%